Changes in glutamine synthetase activity in presence of aluminium complexes - Kertész, Sándor (Acta Biologica Szegediensis, 2002)
In acidic soil release of aluminium (Al) from the solid phase in the rhizosphere is a stress for plants. The pH strongly influences speciation of Al(lll), leading to distinct changes in Al phototoxicity. A hypothesised mechanism of Al tolerance is the chelation and detoxification of Al(lll) by organic acids. Internal or external complex formation determines the behaviour of Al in the cell. Some natural and synthetic compounds were tested in glutamine synthetase (GS, EC 6.3.1.2) assay. GS (total) was extracted from leaves and roots of common wheat (Triticum aestivum L.) grown hydroponically. Magnesium activates both form of GS, but the enzyme activity shows characteristic changes along the Mg2+ concentration range (0-32 mM). Our results confirmed the well-known protective role of citrate and malate, but presented a group of Al(lll)-complexes, which activated the GS. In this group the ligand itself had no effect on reaction, however the AI(lll)-complex enhanced the GS activity, even in lowMg2+ samples. Despite of this stimulation, Al3+ could not substitute Mg2+ in the suboptimal Mg2+range , an d it was not a competitor either.